2018
DOI: 10.1200/jop.18.00121
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful and Accurate Disclosure of Conflict of Interest at the ASTRO National Meeting: A Need for Reassessment of Current Policies

Abstract: Purpose: Conflict of interest (COI) disclosure is essential to research integrity. The average reading comprehension in English is 3.8 words per second (wps). This study examines presenters at the American Society for Radiation Oncology (ASTRO) national meeting over a recent 3-year period to determine whether disclosure is presented accurately and in a manner that allows the audience to comprehend the content. Methods: We examined videos of presentations as well as slides from 2014 to 2016 from the ASTRO virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“… 70 , 71 However, their impact on research results is unclear, with one study finding no significant relationship between company-funded grants and clinical trial outcomes. 52 Further, sometimes undisclosed research payments are more common than undisclosed general payments, 72 but the opposite has also been observed. 55 , 57 , 73 …”
Section: Introductionmentioning
confidence: 99%
“… 70 , 71 However, their impact on research results is unclear, with one study finding no significant relationship between company-funded grants and clinical trial outcomes. 52 Further, sometimes undisclosed research payments are more common than undisclosed general payments, 72 but the opposite has also been observed. 55 , 57 , 73 …”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies have found discrepancies between payments reported in the OPD and self-reported COIs. 16,20 The OPD could improve COI accuracy to promote integrity, transparency, and honesty. Studies examining the COI disclosures of published surgeons in relation to reported payments in the OPD have proposed the implementation of journal-/conference-specific guidelines to prevent confusion regarding what constitutes COIs.…”
Section: Discussionmentioning
confidence: 99%
“…The International Committee of Medical Journal Editors (33) and most professional medical societies (eg, ACOG and the American Society of Clinical Oncology [34,35]) have disclosure policies for investigators considering publication or presentation of research findings. Despite these disclosure policies, conflicts are likely underreported and misreported (36)(37)(38). In one recent prominent case, a senior physician-scientist received millions of dollars of personal income from industry sponsors of his clinical research and failed to disclose this tie to industry in "dozens" of high-profile publications (39).…”
Section: Disclosure Of Industry Involvement In Publications and Prese...mentioning
confidence: 99%